Corporate Social Responsibility and Firm Financial Performance: A Case of SME’s Sector in Pakistan. - Waqas Ahmad WATTO; Daniel T H MANURUNG; Komang Adi Kurniawan SAPUTRA; Syed Gulam MUSTAFA (International Journal of Environmental, Sustainability, and Social Science, 2020)
The paper assesses its relationship with firm innovation and Organizational performance in a single integrative model by using spss data set of 53 Pakistani SME’s firms. A questionnaire of self-administrative is developed to collect the data. Researcher personally visits of different SME’s firms and collect the data from manager of SME’s firms. The research use 275 questionnaire is distributed in different SME’s sector. In this study the statistical techniques of data analysis are used to investigate and find out the relationship among the Firm performance and the other factors. SPSS version16 is used for reliability analysis, descriptive statistics, regression analysis, correlation analysis, to check either modal is good fit or not. Our results supports a partial mediation effect of innovation performance on the relationship between corporate social responsibility and firm performance, meanwhile the effect of corporate social responsibility on firm performance shrinks upon the adding of innovation performance to the model. The findings may help to understand how corporate social responsibility is an important driver mechanism for companies to be more inventive, proficient and effective.